GFAAS Determination of Zinc in Fish Feed and Feces Using Slurry Sampling - Dib Saleh, Mayra Anton [UNESP]; Ferreira Neves, Renato de Cassio [UNESP]; Silva, Fabio Arlindo [UNESP]; de Moraes, Paula Martin [UNESP]; Loureiro, Vanessa Rosa [UNESP]; Roldan, Paulo dos Santos; Padilha, Pedro de Magalhaes [UNESP] (Springer, 2009)
This paper presents a simple, fast, and sensitive method to determine zinc in samples of feces and fish feed by electrothermal atomic absorption spectrometry through the direct introduction of slurries of the samples into the spectrometer's graphite tube. The procedure is based on the injection of 10 mu L of an acidified aqueous solution containing 0.50% w/v of feces or feed and 0.50% v/v HNO(3) into graphite tube. The limits of detection and quantification calculated for 20 readings of the blank of the standard slurries (0.50% w/v of feces or feed devoid of zinc) were 0.04 and 0.13 mu g L(-1) for the standard feces slurries and 0.05 and 0.17 mu g L(-1) for the standard feed slurries. The proposed method was applied in studies of digestibility of zinc in different fish feeds, and their results proved compatible with that obtained from samples mineralized by acid digestion using microwave oven.
Keywords: AAS; Sampling; Process Analysis; Biological Samples; Fish Nutrition